KETERKAITAN ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY PADA BERBAGAI PERISTIWA PEMILU - Rahma Nur Praptiwi; Tri Widjatmaka (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2021)
This research is an event study that aims to find out whether there is empirical evidence of the reaction of the Indonesian capital market to political events in the country, namely the 2015 Regional Head Election, 2014 Presidential Election, and 2020 US Presidential Election, using abnormal return indicators and trading volume activity. The population in this study are stocks that are included in the top 10 capitalization companies in Indonesia. The data used in this study is secondary data consisting of daily stock prices, daily stock trading volume, and daily stock price index for five days before and five days after the incident. The statistical tool used to test the hypothesis is the paired sample t-test. The results of the statistical calculation of the paired sample t-test both abnormal return and trading volume activity show that there is no difference in the average abnormal return and trading volume activity before and after the event